Measurement of Stock Portfolio Performance Based on Risk Adjusted Return on Jakarta Islamic Index (JII) Stock - Komang Tri Wahyuni (International Forum of Researchers and Lecturers, 2024)
Research of stock portfolio performance based on market to book value (PBV) and market capitalization are still a debate and pro kontra. The purpose of this research is to analyze the performance of stock portfolio based on PBV and market capitalization. The samples of this study Jakarta Islamic Indeks (JII) during periode 2020-2022. Total Observation of 60 was determined by purposive sampling method. Performance of stock portfolio based on PBV is devided by 2 format stock portfolios, namely: PBV high and PBV low. For market capitalization is devided by 2 format stock portfolio namely : big market capitalization and small market capitalization. All of them are measured by Risk Adjusted Return (index of Sharpe and Treynor). The result of these research is stock portfolio performance namely PBV low is outperform than PBV high, big market capitalization and small market capitalization which measured by index Sharpe and index Treynor during periode 2020 – 2022 at Jakarta Islamic Indeks (JII). The implication of this study suggests to perform of stock performance namely PBV low which havethe potential high earning growth because PBV less than one, means undervalued.